2012
DOI: 10.1037/a0022247
|View full text |Cite
|
Sign up to set email alerts
|

Male academic performance in college: The possible role of study strategies.

Abstract: There is growing concern among some commentators regarding the academic preparation and performance of male college students in the United States (Wilson, 2007). In this study, gender differences in approaches to learning and study strategies were examined in three samples of community college and university students (N ϭ 650; 274 men, 376 women) utilizing two instruments. Significant multivariate effects for gender were found for both approaches to learning and study strategies. Women scored significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 30 publications
(50 reference statements)
5
28
0
2
Order By: Relevance
“…Statistically significant gender differences in course grades throughout the freshman year of college coursework were found but with no obvious cause (Keller et al, ). In contrast, Yates and James () found male medical students were at a greater risk of struggling than females, and other studies found female students were more likely to use effective study methods, better manage their time and seek formative feedback (Sinclair and Cleland, ; Marrs and Sigler, ). Others found no significant gender bias when predicting course grades in introductory undergraduate courses with traditional predictors of success (aptitude tests, high school grades, etc.,) (McCornack and McLeod, ).…”
Section: Discussionmentioning
confidence: 94%
“…Statistically significant gender differences in course grades throughout the freshman year of college coursework were found but with no obvious cause (Keller et al, ). In contrast, Yates and James () found male medical students were at a greater risk of struggling than females, and other studies found female students were more likely to use effective study methods, better manage their time and seek formative feedback (Sinclair and Cleland, ; Marrs and Sigler, ). Others found no significant gender bias when predicting course grades in introductory undergraduate courses with traditional predictors of success (aptitude tests, high school grades, etc.,) (McCornack and McLeod, ).…”
Section: Discussionmentioning
confidence: 94%
“…Previous research indicates that men and women might differ in their time management skills, social behaviours and stressors. For instance, college women report better time management skills than college men (Marrs & Sigler, ). Women tend to be more prosocial, and also more socially anxious and depressed than men, whereas men tend to be more aggressive than women (Rose & Rudolph, ).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…However, female students receive higher grades and graduate from university at a higher rate than male students do (Buchmann & DiPrete, 2006), and women also seem to have better study habits than men do (Noel-Levitz, 2007). Marrs and Sigler (2011) found that women tend to use a deep approach to a higher degree than men do at university, and they discussed this finding in terms of gender socialization, claiming that different socialization experiences cause men and women (boys and girls) to adopt different values. Because of these differences in values, female and male students differ in the extent to which they prepare for exams as well as in how they value the achieved grades.…”
Section: Introductionmentioning
confidence: 99%